THE INFLUENCE OF LEARNING MOTIVATION TOWARD STUDENT ACHIEVEMENT LEARNING CLASS V SD CAMPANG THREE WEST LAMPUNG: Case Studies on IPS Subjects - Rendy Saputra (Universitas Nahdlatul Ulama Lampung, 2018)
This study aims to find a picture related to the influence of learning innovation on student achievement in SD N Campang Tiga, West Lampung. This study aims to: 1) find out the picture of student motivation in SD N Campang Tiga West Lampung, 2) to find a picture of student achievement in SD N Campang Tiga West Lampung, and 3) to find out how much influence the motivation to learn on student achievement at SD N Campang Tiga, West Lampung. The study was conducted using a quantitative approach to answer initial hypotheses (H0) there was no positive and significant effect between learning motivation on student achievement, and / or (H1) there was a positive and significant effect between learning motivation on student achievement. The results of data analysis showed that learning motivation had a positive and significant effect on student achievement with an influence of 18.2% and the rest (81.8%) was influenced by other factors.